EFFECT OF ADDING PINEAPPLE PEEL PENGARUH PENAMBAHAN EKSTRAK KULIT NANAS TERHADAP EFISIENSI PEMANFAATAN PAKAN DAN LAJU PERTUMBUHAN BENIH IKAN KAKAP PUTIH (Lates calcarifer): Bahasa Indonesia - Pratiwi, Dwi Indah; Lestari, Dewi Putri; Diniarti, Nanda (Journal of Fish Nutrition, 2023)
Baramundi (Lates calcarifer) is a leading commodity in Indonesia, but it faces challenges in terms of feed efficiency. Feed is a key factor in determining production costs. Feed efficiency in fish will increase if the feed provided can be well-digested by the fish, allowing the energy obtained from the feed to be optimization. One effort to achieve this is by using pineapple peel waste as a source of the enzyme bromelain. The objective was to analyze the effect of adding pineapple peel extract on growth, feed utilization efficiency, digestion time, and the optimal dosage given to white snapper (Lates calcarifer). This research used an experimental method with a Completely Randomized Design (CRD). The aspects studied were the effectiveness of adding pineapple peel extract at different dosages to the feed with four treatments and four repetitions, resulting in 16 experimental units. P1 was without the addition of pineapple peel extract (control), P2 with the addition of 25 ml of pineapple peel extract per kg of feed, P3 with the addition of 50 ml of pineapple peel extract per kg of feed, and P4 with the addition of 75 ml of pineapple peel extract per kg of feed. Based on the results of the research concluded that adding pineapple peel extract at different dosages to the feed had a significantly different effect on absolute weight growth, absolute length growth, feed conversion, feed utilization efficiency, and stomach emptying time in white snapper. However, the addition of pineapple peel extract at different dosages to the feed did not have a significantly different effect on the survival rate of common carp. The best values in each test parameter were found in the treatment with adding 50 ml of pineapple peel extract per kg of feed